(untitled) (Colloquia Comparativa Litterarum, 2025)
“The Polyphonic Potential of Gender Studies” – Sociological Problems, The Institute for the Study of Societies and Knowledge at Bulgarian Academy of Sciences, 2018, No 2/50. https://www.ceeol.com/search/journal-detail?id=760